GC-Content of Synonymous Codons Profoundly Influences Amino Acid Usage - Li, Jing (G3 (Bethesda), 2015)
Amino acids typically are encoded by multiple synonymous codons that are not used with the same frequency. Codon usage bias has drawn considerable attention, and several explanations have been offered, including variation in GC-content between species. Focusing on a simple parameter—combined GC proportion of all the synonymous codons for a particular amino acid, termed GC(syn)—we try to deepen our understanding of the relationship between GC-content and amino acid/codon usage in more details. We analyzed 65 widely distributed representative species and found a close association between GC(syn), GC-content, and amino acids usage. The overall usages of the four amino acids with the greatest GC(syn) and the five amino acids with the lowest GC(syn) both vary with the regional GC-content, whereas the usage of the remaining 11 amino acids with intermediate GC(syn) is less variable. More interesting, we discovered that codon usage frequencies are nearly constant in regions with similar GC-content. We further quantified the effects of regional GC-content variation (low to high) on amino acid usage and found that GC-content determines the usage variation of amino acids, especially those with extremely high GC(syn), which accounts for 76.7% of the changed GC-content for those regions. Our results suggest that GC(syn) correlates with GC-content and has impact on codon/amino acid usage. These findings suggest a novel approach to understanding the role of codon and amino acid usage in shaping genomic architecture and evolutionary patterns of organisms.